Pengaruh Ketersediaan Fasilitas Kampus terhadap Motivasi Belajar Mahasiswa Fakultas Ilmu Dakwah dan Komunikasi UIN Syarif Hidayatullah Jakarta - Fatah, Fauzan Nurul; Khairaini, Najwa; Atthoriq, Saqif Azziyad; Camelia, Silvie (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The availability of campus facilities is one of the aspects that is believed to support student learning activities. However, the extent to which these facilities affect learning motivation still needs to be further researched. This study aims to determine the effect of the availability of campus facilities on the learning motivation of students of the Faculty of Da'wah and Communication Sciences (FDIKOM) UIN Jakarta. A quantitative approach was used in this study with a survey method of 27 respondents. The research instrument was tested for validity and reliability before data analysis was carried out. Of the nine items on the campus facility variable, only five items were valid and used in the subsequent analysis. The results of the descriptive analysis showed that both the availability of facilities and learning motivation were in the medium category. A simple regression test showed a determination coefficient value (R²) of 0.032, which means that only 3.2% of the variation in learning motivation can be explained by campus facilities. In addition, the results of the t-test showed that campus facilities did not have a significant effect on student learning motivation (p > 0.05). Although the direction of the relationship is positive, the influence is not statistically strong enough. These findings indicate that increasing student learning motivation cannot depend solely on campus facilities, but needs to involve other factors such as academic support, learning strategies, and psychological aspects of students. This research contributes to understanding the factors that influence learning motivation and recommends further studies with a wider scope.